DNA Methylation Fluctuation Induced by Virus Infection Differs between MD-resistant and -susceptible Chickens - Luo, Juan; Yu, Ying; Tian, Fei; Zhang, Huanmin; Chang, Shuang; Song, Jiuzhou (Frontiers in Genetics, 2012)
Marek’s disease (MD) is a lymphoproliferative disease induced by Marek’s disease virus (MDV) infection. With the less efficacy of vaccine in MD prevention, genetically selected MD-resistant chicken becomes more and more important in MD control. To elucidate the mechanism of MD-resistance, lots of researches were focused on the different genetic differences between the resistant and susceptible chickens. However, less is known about the epigenetic features. By using pyrosequencing, the promoter methylations of 18 candidate genes in MD-resistant (L63) and –susceptible (L72) chicken were examined, we found that most of the genes have higher methylation level in L72. MDV infection changed the expressions of all three methyltransferases (DNMT1, DNMT3a and DNMT3b), while the up-regulation of DNMT1 was only shown in L72 and down-regulation of DNMT3b only in L63 at 21dpi. Interestingly, a dynamic change of promoter methylation was observed in most of the genes in both lines during MDV life cycle. Seven genes, including HDAC9, GH, STAT1, CIITA, FABP3, LATS2 and H2Ac, showed different methylation behavior between L63 and L72. In summary, the findings from this study suggested that DNA methylation heterogeneity exists in MD-resistance and –susceptibility chicken, and MDV infection also induces differential methylation alterations, both indicating epigenetic factor may involve in MD.